Perilaku Bullying pada Siswa Sekolah Dasar Islam Cokroaminoto 01 Kalabahi - Astri Rosita Mau Sally; Jeremia S. Wabang; Nur Fitra Manikita; Abdul Hamid Niwang; Zainal M. Sengadji (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses a case study of bullying behavior in elementary schools. Bullying also has a negative impact on victims and this research uses a descriptive qualitative approach to describe this fact. The research method uses observation and interviews. The research results show that bullying can occur in various forms including verbal, physical and nonverbal. Many students in elementary school experience or witness incidents of bullying, which can cause serious psychological impacts. Factors such as students' socio-economic background also influence the high number of bullying cases in schools. Bullying behavior can have a negative impact on the social aspects of students in elementary schools. Efforts to prevent and handle bullying in elementary schools need to involve collaboration between schools and parents. Most of the references used in research are primary literature and are up to date.